Consensus Building in Social Marketing Campaigns Through the Delphi Method. (December 2017) - Borden, D. Scott; Shaw, Gareth; Coles, Tim
This article investigates the application of the Delphi method as a tool for building stakeholder consensus on the impact and prioritization of campaign initiatives as applied in a campaign to promote water efficiency behavior. To date, use of the Delphi method has been underutilized and not yet applied to evaluating and prioritizing social marketing initiatives. Ten potential initiatives were developed during previous research, aiming to promote water efficiency in tourism accommodation. A Delphi panel of experts ( n = 21) in tourism, water, and social marketing evaluated, prioritized, and rated the importance of factors used for prioritizing each initiative. Three initiatives received the greatest level of prioritization and were considered to have the highest effectiveness to reach project goals. In the context of this research, a Delphi consultation was a viable method toward this application. Best practices and limitations unique to the social marketing process are offered to aid future social marketing efforts in applying the Delphi method.